14C Age Offset in the Mar Piccolo Sea Basin in Taranto (Southern Italy) Estimated on Cerastoderma Glaucum (Poiret, 1789). Issue 5 (October 2019) - Quarta, Gianluca; Fago, Paola; Calcagnile, Lucio; Cipriano, Giulia; D'Elia, Marisa; Moretti, Massimo; Scardino, Giovanni; Valenzano, Eliana; Mastronuzzi, Giuseppe
ABSTRACT: The stratigraphic succession of the Mar Piccolo basin (Gulf of Taranto, Southern Italy) is well known in the scientific literature dealing with the last interglacial since its morphological evolution is influenced by sea level changes during Late Pleistocene-Holocene. The local Holocene sea level history is well known thanks to data deriving from peat and ash layers identified in different sediment cores obtained underwater and in coastal areas. Peat sediments are frequently interlayed with muddy-sand beds rich in Cerastoderma glaucum (Poiret, 1789). In the literature of the Mediterranean basin, AMS 14 C dating on C. glaucum is widely used also in paleo-environmental reconstruction because this bivalve is considered an useful marker of sea level, though in lagoonal systems, large age offsets have been reported in different areas. Due to the availability of precise chronological and geochronological markers, in order to validate the use of C. glaucum in paleo sea level reconstruction, AMS 14 C dating campaign was carried out on this bivalve deriving from several cores drilled in the Mar Piccolo basin and its nearby areas. Nineteen AMS 14 C dating analyses carried out on C. glaucum sampled from different sediment cores up to a maximum of 30 m from the seafloor are presented. These results show an inconsistency of the ages in relation to a sea-level rise reconstruction model. The interpretation of the data was performed after the estimation of the local age offset calculated by analyzing six live samples, collected in 2017 in Mar Piccolo and in Croatia, and two samples dated to 1968–1969. The results show that for both the classes of samples (2017 and 1960s) an age offset ranging from 600 to 800 yr can be estimated.